1999
DOI: 10.1126/science.286.5448.2361
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Cell Wall Precursor Lipid II by a Pore-Forming Peptide Antibiotic

Abstract: Resistance to antibiotics is increasing in some groups of clinically important pathogens. For instance, high vancomycin resistance has emerged in enterococci. Promising alternative antibiotics are the peptide antibiotics, abundant in host defense systems, which kill their targets by permeabilizing the plasma membrane. These peptides generally do not act via specific receptors and are active in the micromolar range. Here it is shown that vancomycin and the antibacterial peptide nisin Z use the same target: the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
603
0
13

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 718 publications
(632 citation statements)
references
References 16 publications
16
603
0
13
Order By: Relevance
“…Their data support a model in which membrane patches containing sphingolipids act as specific binding sites for defensins or, alternatively, are required to anchor membrane-or cell wall-associated proteins, which themselves interact with defensins (Thevissen et al, 2000a). Similarly, the protein antibiotic nisin Z from Lactococcus lactis binds with high affinity to the membrane-anchored cell wall precursor lipid II of Gram-positive bacteria (Breukink et al, 1999). Like harpin Psph (Lee et al, 2001), nisin Z is an amphipathic, highly charged protein.…”
Section: A Harpin Binding Site Involved In Pr Gene Expression In Tobaccomentioning
confidence: 63%
See 1 more Smart Citation
“…Their data support a model in which membrane patches containing sphingolipids act as specific binding sites for defensins or, alternatively, are required to anchor membrane-or cell wall-associated proteins, which themselves interact with defensins (Thevissen et al, 2000a). Similarly, the protein antibiotic nisin Z from Lactococcus lactis binds with high affinity to the membrane-anchored cell wall precursor lipid II of Gram-positive bacteria (Breukink et al, 1999). Like harpin Psph (Lee et al, 2001), nisin Z is an amphipathic, highly charged protein.…”
Section: A Harpin Binding Site Involved In Pr Gene Expression In Tobaccomentioning
confidence: 63%
“…Like harpin Psph (Lee et al, 2001), nisin Z is an amphipathic, highly charged protein. Remarkably, nisin Z exerted its biological function through high affinity binding to lipid II and subsequent formation of an ion-conducting pore (Breukink et al, 1999).…”
Section: A Harpin Binding Site Involved In Pr Gene Expression In Tobaccomentioning
confidence: 99%
“…Compounds 2a-d were purified using reversed-phase HPLC according to modified literature procedure 13 and characterized by high field 1 H NMR spectroscopy and mass spectrometry (MS). The attachment of the ligands to the C-terminal of Van 4 ] 10+ , the activity of the mixture of 2d and Zn-(OAc) 2 (4:1, at pH ) 7) against VRE is the same as that of 2d, suggesting that there is no multivalent Van formed by metal complexation when 2d and Zn(OAc) 2 react at the condition of the in vitro experiment. We also did not observe the formation of [Zn(2d) n ] (2n+2)+ (n ) 1-4) by ESI-MS, which is consistent with the observed activity.…”
Section: Resultsmentioning
confidence: 88%
“…Studies have also suggested that more specific interactions within bacterial cell walls or membranes help to define antimicrobial peptide activity (38). For example, binding of the antimicrobial peptide nisin can be mediated by peptidoglycan-associated lipid II (39), and salivary histatins bind a 67-kDa surface protein of Candida albicans (40). Specific cell wall/membrane targeting may explain some of the differences in the spectrum of K6A-derived peptide activity, e.g., the 19-mer is effective against S. pyogenes but not S. aureus or E. coli, both of which are highly susceptible to the 14-mer.…”
Section: Discussionmentioning
confidence: 99%